2021
DOI: 10.3390/soc11010019
|View full text |Cite
|
Sign up to set email alerts
|

Designing the Participation on Local Development Planning: From Literature Review to Adaptive Framework for Practice

Abstract: This exploratory review of the literature provides a comprehensive overview of the settings that are available to the planner when managing participatory strategic planning of spatial socio-economic development on the local level. We contextualize individual potential configurations of participation in local development planning practice, documented in a number of case studies from different parts of the world, in order to reflect the multidimensionality of the participatory planning process. These reflections… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 85 publications
0
3
0
Order By: Relevance
“…However, without creating guidelines and frameworks for public participation, the benefits of engaging with stakeholders in planning can be counterproductive. This is also reflected in [67], who compare several case studies of participation that had been conducted without guidelines, and observed instances of tokenistic, and overly open participation, that resulted in unrealistic action plans, formulation of goals that did not reflect the needs of community members, and conflicts between local stakeholders and authorities.…”
Section: The Policy Language Is Non-bindingmentioning
confidence: 98%
“…However, without creating guidelines and frameworks for public participation, the benefits of engaging with stakeholders in planning can be counterproductive. This is also reflected in [67], who compare several case studies of participation that had been conducted without guidelines, and observed instances of tokenistic, and overly open participation, that resulted in unrealistic action plans, formulation of goals that did not reflect the needs of community members, and conflicts between local stakeholders and authorities.…”
Section: The Policy Language Is Non-bindingmentioning
confidence: 98%
“…Participatory approaches have to be shaped according to specific settings in order to be meaningful (Reed, 2008). The nature of these settings is wide-ranging and fluctuates between contextual factors (such as economic, political, social, or linked to the urban project) and technical parameters (e.g., selected medium, visual representation, immersion, device); also, human factors play an active role in the design of the approach (according to the affinity or the experience of the team in charge of designing the approach; Bouzguenda et al, 2020;Bryson et al, 2012;Hrivnák et al, 2021;Ling et al, 2009;Luciano et al, 2018;Sieber, 2006). Digitally generated 3D visual tools as vehicles for the interaction during participatory sessions reflect these various aspects.…”
Section: Compared Aspects and Typologymentioning
confidence: 99%
“…Therefore, the organization of events and festivals represents, both for residents and for visitors, many opportunities which can be educational, cultural and also economic, manifesting themselves in a positive and beneficial way [44,45]. On the other hand, the organization of these events and festivals improves people's health through relationships and social interactions [46], and facilitates the exchange of ideas between communities and how they communicate, with the end result reducing depression and loneliness and allowing individuals to acquire a sense of belonging to a community and a place [47,48], but also creating the premises for better participation of both rural residents and stakeholders in order to build a viable and sustainable local development strategies [48]. Studies which approach and analyze community perceptions of sustainable tourism development [3,[49][50][51][52][53][54][55] usually consider three dimensions (economic, environmental and socio-cultural) as a whole, and rarely focus on a specific one, such as the socio-cultural dimension, as a key element for gaining community support.…”
Section: Impact Of Tourism Festivals On the Local Rural Communitiesmentioning
confidence: 99%